Global South perspectives: a curriculum analysis of a global North comparative international education graduate program - Casellato, Mariana (Revista Española de Educación Comparada, 2023)
The field of Comparative International Education trains new professionals every year who engage in work in diverse countries around the world, especially global South countries, influencing policy decisions. At the same time, the decolonization framework points out the epistemic dominance of the North, which faces the ‘other’ as an object of study rather than a subject capable of also producing knowledge. This study aims to use the framework of modernity/coloniality/decoloniality to understand the profile diversity of the authors used within the training of Comparative International Education (CIE) professionals in the Global North. It presents a bibliometric analysis of the syllabi of three offerings of the basic requirement course of the International Educational Development program at Teachers College Columbia University for the academic year of 2019-2020, evaluating the presence of Global South authors. Using basic descriptive statistics and social network analysis, this study investigates the geographic representation of the canons in the field by tracing the authorship of course readings. The findings demonstrate that research produced within the Global North is dominant in the basic training of CIE students, whereas Global South authors are present almost five times less than their Global North counterparts.